Adesão à terapia antirretroviral de pais e filhos atendidos no Hospital Universitário de Santa Maria - Bertoncello, Marceli Zamboni (2013)
The introduction of highly active antiretroviral therapy (HAART) has changed the course of Acquired Immunodeficiency Syndrome (AIDS), from a fatal into a chronic disease, providing a significant improvement in quality of life of people living with HIV and also their families. However, adherence to antiretroviral therapy is the most important determinant of survival of HIV-infected individuals, requiring high levels of adherence to adequate virologic response. In Brazil, few studies have been conducted on the treatment of children infected with HIV. This study evaluated treatment adherence to antiretroviral therapy between parents and biological children. We interviewed 25 pairs of parents and children in the outpatient clinic to Mother and Child at Santa Maria University Hospital - RS. After the medical routine appointment, the parents answered a questionnaire with questions about the sociodemographic conditions and clinical profile of patients. Adherence to treatment was defined as parents and children ingested more than 95% of prescribed medications in the 48 hours preceding the interview. The adherence of parents and children reported was 84%. Among the 21 parents with adherence > 95%, 10 (47,6%) had an undetectable viral load between 21 and, between 21 adherent children, 13 (61,9%). There was association between adherence to therapy between parents and child (P <0,05). It can be concluded that parents and children are mostly adherent to antiretroviral therapy. However, although the parents have reported treatment adherence was not associated with an undetectable viral load, showing that the information may be flawed. We also found a higher percentage of undetectable viral load in children when compared to their parents, inferring a greater commitment of parents to treat their children than their own.